Religion, ideology, and counter-culture : essays in honour of S. Kappen - Mathew, Philip; Muricken, Ajit; Kappen, Sebastian (Bangalore, India, Horizon Books in association with Asha Kendra, 1987)
Festschrift honoring Sebastian Kappen, b. 1924, theologian; comprises articles on theology
Keywords: Religion and Culture